Dendritic cells during the HIV-1 infection. (Colombia Medica, 2007)
Dendritic cells are components of the innate immunity crucial for activating naïve T cells. They are one of the target cells for HIV-1 infection, but their ability to replicate HIV-1 is much more limited than that exhibited by CD4+ T cells. However, they have the capacity to store the virus for long periods of time which are able to infect susceptible cells later on. Therefore, dendritic cells are considered as one of the most important reservoirs for the HIV-1. At early stages of this infection, dendritic cells also contribute with the anti-HIV-1 immune response, but then they exhibit quantitative and functional alterations enhancing the severe immunodeficiency characteristic of this infection. The important role of dendritic cells in inducing innate and adaptive immune responses indicates that these cells have a promising therapeutic potential for the development of vaccines and immunotherapy for HIV-1 infection.